Bank Credit in Argentina in the Aftermath of the Mexican Crisis : Supply or Demand Constrained? - Catao, Luis (IMF Working Papers; Working Paper, 1997)
Liquidity in the banking sector in Argentina reached new heights in early 1996 with the sharp reflow of deposits in the aftermath of the 1995 banking crisis. Yet, this did not translate into a similar recovery of credit to the private sector. Two hypotheses have been raised to explain this mismatch. One is that credit to the private sector was supply constrained because of adverse selection mechanisms exacerbated by the crisis. An alternative hypothesis is that credit was demand constrained, as unemployment remained high and the debt stock adjustment unwound only slowly through the first half of 1996. This paper examines these hypotheses.